Action Research to Develop and Validate a Scheme of Work to Promote Creativity and Designerly Thinking Through Play - Danos, Xenia; Constantinou, Constantinos P.; Livitzis, Michalis; Avraam, Cristakis (Design and Technology Education: An International Journal, 2014)
The paper reports on a study of the development and validation of a Design and Technology Scheme of Work (SoW) that is facilitated by Engino assembly toys. Three initial case studies are described; one to assess the suitability of the Engino products for specific age groups; and two which took place in primary schools; one to evaluate the sequence of tasks designed for the actionresearch case study; and another to investigate if creativity can be promoted through the Engino products. Two further action research case studies were then completed with secondary school students, during which the SoW was further developed and elaborated to suit the needs of this age group. The final versions of the SoW were further validated during a dissemination seminar and professional development workshops involving primary and secondary school teachers. Having the importance of play in mind for enthusiastic and creative learning, the SoW was designed to fulfil a number of requirements from the Cypriot National Curriculum, covering 6 of the 9 areas. We discuss our findings with reference to promoting creativity in the context of Design and Technology as well as the possible roles that construction toys can play in this endeavour. The paper is illustrated with a picture gallery with indicative examples from student work.